2020
DOI: 10.3389/fonc.2020.00131
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Impact of Surgical Excision on Overall Survival in Primary Central Nervous System Lymphoma

Abstract: Substantial controversy still exists regarding the use of surgical excision in the treatment of primary central nervous system lymphoma (PCNSL). This study was aimed to evaluate the survival benefit of surgical excision in PCNSL patients based on a US population. Using the Surveillance, Epidemiology, and End Results (SEER) Program database, a total of 3,543 PCNSL patients were identified from 2000 to 2014 for analysis. Surgical excision was accessed via Kaplan-Meier and multivariate Cox regression survival ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…To better understand the pattern and mechanism of relapse, we reviewed 27 relapsed patients who attained complete response (CR), partial response (PR) or stable disease (SD) during or after first-line treatment without WBRT for newly diagnosed PCNSL in our institution. We found more than half of the patients had distant recurrence and among those reached CR patients, 9/11(82%)had distant recurrence as well, which are comparable to those described with intravenous HD-MTX (12/16, 75%) 33 and those with intra-arterial HD-MTX in conjunction with blood-brain barrier disruption (BBBD) 50 (30/37, 80%).Recently, a number of studies [51][52][53][54][55] have shown that surgery may be beneficial for PCNSL patients. It is worth noting that 8 of the 11patients who achieved CR by receiving GTR, eventually relapsed with DR, which reminds us that there may be subclinical CNS lymphomas which contrast enhanced MRI cannot to detect.…”
Section: Pcnsl Is a Rare Extra-nodal Lymphoma With Aggressive Clinicasupporting
confidence: 77%
“…To better understand the pattern and mechanism of relapse, we reviewed 27 relapsed patients who attained complete response (CR), partial response (PR) or stable disease (SD) during or after first-line treatment without WBRT for newly diagnosed PCNSL in our institution. We found more than half of the patients had distant recurrence and among those reached CR patients, 9/11(82%)had distant recurrence as well, which are comparable to those described with intravenous HD-MTX (12/16, 75%) 33 and those with intra-arterial HD-MTX in conjunction with blood-brain barrier disruption (BBBD) 50 (30/37, 80%).Recently, a number of studies [51][52][53][54][55] have shown that surgery may be beneficial for PCNSL patients. It is worth noting that 8 of the 11patients who achieved CR by receiving GTR, eventually relapsed with DR, which reminds us that there may be subclinical CNS lymphomas which contrast enhanced MRI cannot to detect.…”
Section: Pcnsl Is a Rare Extra-nodal Lymphoma With Aggressive Clinicasupporting
confidence: 77%
“…A new nomogram model (Fig. 4) was established, which may offer an individualized quantitative potential benefit from surgical excision to patients with PCNSL (136). The nomogram model was internally validated using the bootstrap validation method.…”
Section: Combined Surgery and Chemotherapy Or Rtmentioning
confidence: 99%
“…4C). This practical clinical tool may provide more distinct and direct data to assist clinical decision-making and optimization of therapeutic approaches in clinical care (136).…”
Section: Combined Surgery and Chemotherapy Or Rtmentioning
confidence: 99%
See 2 more Smart Citations